Elderflora : a modern history of ancient trees - Farmer, Jared, 1974- (Basic Books, Hachette Book Group, 2022)
Humans have always revered long-lived trees. But as historian Jared Farmer reveals in Elderflora, our veneration took a modern turn in the eighteenth century, when naturalists embarked on a quest to locate and precisely date the oldest living things on earth. The new science of tree time prompted travelers to visit ancient specimens and conservationists to protect sacred groves. Exploitation accompanied sanctification, as old-growth forests succumbed to imperial expansion and the industrial revolution. Taking us from Lebanon to New Zealand to California, Farmer surveys the complex history of the world's oldest trees, including voices of Indigenous peoples, religious figures, and contemporary scientists who study elderflora in crisis. In a changing climate, a long future is still possible, Farmer shows, but only if we give care to young things that might grow old. --